2020
DOI: 10.28991/cej-2020-sp(emce)-09
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nonlinear Fluid Viscous Dampers on Seismic Response of RC Elevated Storage Tanks

Abstract: The numerical investigation on the seismic response of RC elevated liquid storage tanks installed with viscous dampers is presented. A discrete two-mass model for the liquid and multi-degree of freedom system for staging, installed with the dampers are developed for Reinforced Concrete (RC) elevated liquid storage tanks. The elevated tank is assessed for seismic response reduction when provided with Linear Viscous Damper (LVD) and Nonlinear Viscous Damper (NLVD), installed in the staging. The RC elevated liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The choice of proper i th and j th modes is crucial, i.e., the specified modes should significantly contribute to the structures’ response 35 .
Figure 10 Rayleigh damping 40 .
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of proper i th and j th modes is crucial, i.e., the specified modes should significantly contribute to the structures’ response 35 .
Figure 10 Rayleigh damping 40 .
…”
Section: Methodsmentioning
confidence: 99%
“…As suggested by EC-8, the damping ratios of 0.5 and 5 percent are assigned for the convective and impulsive components, respectively. Furthermore, the stiffness proportional damping equivalent to 5 percent of critical damping is assumed as structural damping 40 .…”
Section: Methodsmentioning
confidence: 99%
“…Their failure mechanism is influenced by a multitude of factors, including the tank's construction material, tank configuration, tank type, and supporting mechanism [1]. Several researchers and practitioner engineers have focused their efforts on assessing the seismic vulnerability of such structures [2].…”
Section: Introductionmentioning
confidence: 99%
“…Waghmare et al [8] considered a numerical investigation in a multi-real earthquake for reinforced concrete elevated tanks in viscous dampers. They found that viscous dampers' nonlinearity and low damping constant contributed a comparable reduction to those viscous dampers with linear and high damping constant.…”
Section: Introductionmentioning
confidence: 99%